2017
DOI: 10.1111/1475-6773.12652
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Drug Monitoring Programs Produce a Limited Impact on Painkiller Prescribing in Medicare Part D

Abstract: Prescription drug monitoring programs have a modest effect targeted at the high-profile drug oxycodone among the Medicare Part D population and an even smaller effect for hydrocodone and opioids in general. The findings suggest some substitution toward lower schedule opioids. Substantially addressing the widespread opioid abuse problem will require enhancing existing PDMPs or implementing new policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…We excluded the following studies from Table because they evaluated PDMP provisions, not overall PDMPs, or compared robust to nonrobust PDMPs: Brown et al, 2017; Gilson et al., 2011; Green et al., 2012; Haffajee et al., 2018; Kuo et al., 2016; Pardo et al., 2016; Phillips et al., 2017; Rasubala et al., 2015; Ringwalt et al., 2015; Sigler et al., 1984; Suffoletto et al., 2018; Sun et al., 2017; Wastila et al., 1996; Wen et al., 2017; and Yarbrough et al., 2018 . See Online Appendix for a detailed summary of these evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded the following studies from Table because they evaluated PDMP provisions, not overall PDMPs, or compared robust to nonrobust PDMPs: Brown et al, 2017; Gilson et al., 2011; Green et al., 2012; Haffajee et al., 2018; Kuo et al., 2016; Pardo et al., 2016; Phillips et al., 2017; Rasubala et al., 2015; Ringwalt et al., 2015; Sigler et al., 1984; Suffoletto et al., 2018; Sun et al., 2017; Wastila et al., 1996; Wen et al., 2017; and Yarbrough et al., 2018 . See Online Appendix for a detailed summary of these evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…A PDMP is a database of certain prescribed and dispensed prescriptions by providers and pharmacies with the goals of monitoring prescribing patterns and doctor shopping behaviors to limit prescription drug misuse and diversion. These data were gathered from Yarbrough, which were originally gathered from the National Alliance for Model State Drug Laws (NAMSDL) and supplemented with additional state‐specific information. While some states have adopted subsequent regulations to their PDMPs such as mandatory use provisions, these policies are rather recent in our data period and vary with respect to which prescription substances trigger a mandated query of the PDMP and at what time intervals the PDMP must queried.…”
Section: Datamentioning
confidence: 99%
“…A PDMP is a database of certain prescribed and dispensed prescriptions by providers and pharmacies with the goals of monitoring prescribing patterns and doctor shopping behaviors to limit prescription drug misuse and diversion. These data were gathered from Yarbrough, 33 and supplemented with additional state-specific information. 18,34 Finally, there is recent evidence that MMLs affect the use and misuse of prescription drugs (and opioids in particular).…”
Section: Re Vie W Of E Xis Ting Liter Aturementioning
confidence: 99%
“…5,6,7,8,9,10,11 One premise of these supply-side interventions is that they will decrease the number of individuals exposed to opioid analgesics and subsequently prevent individuals from developing an opioid use disorder (OUD), ultimately lowering the number of opioid overdose deaths. Previous studies have shown that such interventions may lead to a modest decrease in the prescription opioid supply, especially programs with enrollment and/or use mandates.…”
Section: Introductionmentioning
confidence: 99%